Phylogeography and genetic diversity of the Robin (Erithacus rubecula) in the Azores Islands: Evidence of a recent colonisation - Rodrigues, Pedro (2013)
We present new insights into the phylogeography of the Robin, Erithacus rubecula, from the seven Azores Islands where it breeds, based on sequences of mitochondrial and nuclear genes from 35 individuals (five from each of the seven islands) as well as outgroup/comparison samples from Madeira, Canary Islands and Continental Western Palearctic (Europe and North Africa). To understand the level of concordance between the genetic data and morphometric variability, eight morphometric characters were analysed for 113 birds for the seven Azores Islands populations. Our results revealed that Robins from the Azores possess low genetic diversity and share their most common haplotype with Madeira and the Continental Western Palearctic Robins, which support the hypothesis of one recent founder event and a fast range expansion to most of the Azores Islands. Nevertheless, despite this lack of neutral genetic differentiation, morphological differences were found among islands, which could be attributed to natural selection processes. The morphological data show that birds from Sa˜o Miguel had the longest wings and largest body mass, and that birds from Graciosa had the smallest bill length. This recent colonisation could be the reason for the absence of Robins in the westernmost islands of the Azores.